Experimental Study on Horizontal Flame Spread of Dual-Flame Sources for Building Façade Energy Conservation FPU Foam Under the Effect of Lateral Wind - Zhang, Wei; Wang, Jingwei (Frontiers in Energy Research, 2022)
Thermal safety of building façade energy conservation materials are commonly affected by the wind in the surrounding environment. Additionally, multiple fire sources might be formed because of the secondary ignition of the primary fire source. In this study, the compling effect of dual flame sources and the lateral wind speed ( ) on the typical characteristic parameters (flame morphology, mass loss rate, and heat transfer) of horizontal flame spread behavior of thermal insulation board FPU (Flexible Polyurethane) was investigated through laboratory-scale experiments. Results showed that these parameters didn’t increase or decrease monotonously with the lateral wind speed. The original vertical flame front was stretched and tilted by the effect of lateral wind speed, which increased the area and thermal feedback of the preheating zone on the windward side. On the one hand, the lateral wind promoted the peak flame temperature and shortened the time to the peak temperature. On the other hand, the wind speed promoted average flame spread velocity on the windward side and decreased the average flame spread velocity on the leeward side. The flame was blown out when the wind reached a critical speed. This could be well explained with the mechanism of heat transfer and turbulent flow. This work can provide a reference for the fire rescue and building fire protection regulations.